A Case Report on Pituitary Apoplexy - Jha, Rajiv; Ghimire, Rupak Raj (Journal of Brain and Spine Foundation Nepal, 2021)
Objective: To report a case of pituitary apoplexy presenting with unilateral ptosis and unilateral third nerve palsy in diabetic and hypertensive patient. Clinical Presentation and Intervention: A 50 years old man developed unilateral third nerve palsy. A pituitary macro adenoma with hemorrhagic and necrotic changes on MRI scan was resected by endoscopic transsphenoidal procedure. Third nerve palsy improved promptly and completely few hours postoperatively. Conclusion: This is a rare case of pituitary apoplexy that presented with unilateral third cranial nerve palsy recovered promptly after surgical excision of mass.